Indian Journal of Nematology: Nematode Diseases of Crops and Their Sustainable Management (Indian Journal of Nematology, 2024)
Editors: Mujeebur Rahman Khan and M. Quintanilla2023, 721 + xv pp, Paperback, Price: Rs. 16530Academic Press, Elsevier